Factors associated with medication non-adherence among patients with heart failure - Jannaína Gomes de Lima; Alba Lucia Bottura Leite de Barros; Juliana de Lima Lopes (Universidade de São Paulo, 2024)
Abstract Objective: to identify the factors contributing to medication non-adherence among patients with heart failure. Method: cross-sectional and analytical study using the Medida de Adesão ao Tratamento [Treatment Adherence Measure] scale to assess medication non-adherence. Independent variables were collected using the European Heart Failure Self-care Behavior Scale and an instrument developed by the authors based on a previous study. Statistical tests were implemented to analyze data with p≤0.05 statistical significance. Results: the sample comprised 340 patients, with 9.4% considered non-adherent. The multiple analysis results showed that one unit increase in an individual's self-care score led to an 8% increase in the prevalence of non-adherence; patients with a family income above three times the minimum wage presented a prevalence of non-adherence equal to 3.5% of the prevalence of those with up to one times the minimum wage; individuals consuming alcohol or with depression presented 3.49 and 3.69 times higher prevalence of non-adherence, respectively, than individuals not presenting such history. Conclusion: medication non-adherence was associated with self-care, family income, depression, and alcohol consumption.